Dosimetric Evaluation of Three-Dimensional Conformal Radiation Therapy Breast Cancer Treatment Plans - Kaduga Altwieb; Jalal Eltabib (AlQalam Journal of Medical and Applied Sciences, 2024)
Breast cancer is one of the most common cancers affecting women worldwide. Radiotherapy plays a pivotal role in breast cancer management. This study aims to conduct a comprehensive dosimetric analysis of breast cancer patients undergoing radiotherapy. In this study, 28 breast cancer patients were analyzed for various dosimetric parameters, including D98%, D95%, D50%, D5%, and D2%, as well as maximum, minimum, and mean doses within the PTV. PTV volume coverage was assessed at 95%, 93%, and 91% of the prescribed dose, with hot spot dose volumes at 115%, 110%, 108%, and 105%. Doses to organs at risk (OARs) were also evaluated. Dosimetric indices—uniformity index (UI), conformity index (CI), and homogeneity index (HI)—were calculated to assess treatment quality. Right-sided patients received higher doses at D98% and D95%, with smaller differences at D50%, D5%, and D2%. Left-sided patients had higher mean maximum and mean doses within the PTV, while right-sided patients had higher minimum doses. Left-sided chest wall-only patients showed higher hot spot volumes at 110% and 105%, though all patients had minimal volumes at 115%. Ipsilateral lung V20 was below 35% for all, with higher values in the chest wall and supraclavicular treatments. The mean heart dose was higher for left-sided treatments but stayed below cardiac toxicity limits. UI was slightly better in right-sided "Breast & SC" plans, and CI was higher in right-sided patients, while HI was higher in right-sided "Breast & SC" than left-sided "Breast Only." The study highlights differences in dose distribution between left and right-sided patients, with right-sided cases receiving higher doses at key points and left-sided cases showing larger PTV volumes and greater heart exposure. Dosimetric indices suggest treatment refinement may be needed, particularly for left-sided cases, to improve outcomes and reduce toxicity. سرطان الثدي هو أحد أكثر أنواع السرطان شيوعًا التي تصيب النساء في جميع أنحاء العالم. يلعب العلاج الإشعاعي دورًا محوريًا في إدارة سرطان الثدي. تهدف هذه الدراسة إلى إجراء تحليل شامل للجرعات لمرضى سرطان الثدي الذين يخضعون للعلاج الإشعاعي. في هذه الدراسة، تم تحليل 28 مريضة بسرطان الثدي من أجل معايير قياس الجرعات المختلفة، بما في ذلك D98٪ و D95٪ و D50٪ و D5٪ و D2٪، بالإضافة إلى الحد الأقصى والحد الأدنى والجرعات المتوسطة ضمن PTV. تم تقييم تغطية حجم PTV بنسبة 95٪ و 93٪ و 91٪ من الجرعة الموصوفة، مع أحجام جرعات النقاط الساخنة بنسبة 115٪ و 110٪ و 108٪ و 105٪. كما تم تقييم الجرعات للأعضاء المعرضة للخطر (OARs). تم حساب مؤشرات الجرعات - مؤشر التوحيد (UI) ومؤشر المطابقة (CI) ومؤشر التجانس (HI) - لتقييم جودة العلاج. تلقى المرضى من الجانب الأيمن جرعات أعلى عند D98٪ و D95٪، مع اختلافات أصغر عند D50٪ و D5٪ و D2٪. كان لدى المرضى من الجانب الأيسر متوسط ​​أعلى للجرعات القصوى والمتوسطة داخل PTV، بينما كان لدى المرضى من الجانب الأيمن جرعات دنيا أعلى. أظهر مرضى جدار الصدر الأيسر فقط أحجام نقاط ساخنة أعلى عند 110٪ و 105٪، على الرغم من أن جميع المرضى كان لديهم أحجام دنيا عند 115٪. كان V20 في الرئة من نفس الجانب أقل من 35٪ للجميع، مع قيم أعلى في جدار الصدر والعلاجات فوق الترقوة. كان متوسط ​​جرعة القلب أعلى للعلاجات من الجانب الأيسر ولكنها ظلت أقل من حدود السمية القلبية. كان مستوى مقاومة الأنسولين أفضل قليلاً في خطط "الثدي والحمل تحت الجلد" على الجانب الأيمن، وكان مؤشر كتلة الجسم أعلى لدى المرضى على الجانب الأيمن، بينما كان مؤشر كتلة الجسم أعلى لدى المرضى على الجانب الأيمن "الثدي والحمل تحت الجلد" مقارنة بالمريضين على الجانب الأيسر "الثدي فقط". تسلط الدراسة الضوء على الاختلافات في توزيع الجرعة بين المرضى على الجانب الأيسر والأيمن، حيث تلقت الحالات على الجانب الأيمن جرعات أعلى في نقاط رئيسية وأظهرت الحالات على الجانب الأيسر أحجام PTV أكبر وتعرضًا أكبر للقلب. تشير مؤشرات الجرعات إلى أن تحسين العلاج قد يكون ضروريًا، وخاصة بالنسبة للحالات على الجانب الأيسر، لتحسين النتائج وتقليل السمية